Illuminating how identities, stereotypes and inequalities matter through gender studies - Farris, Demetrea Nicole; Davis, Maryann; Compton, D'Lane R. (D'Lane Rebecca), 1977- (New York : Springer, 2014)
This collection highlights and extends contemporary women's and gender studies by presenting theoretical analyses and innovative research conceptualizations, applications and methodologies via a diverse variety of popular-in-the-classroom topics, such as changing masculinities; comedic/dramatic portrayals of ethnicity and discrimination; stigma and differences within mainstream media gender stereotypes; intersections of gendered and sexual identities in social media and fundamental institutions. These topics emphasize relevant issues and nuances within popular culture, identities and perception.
Part I: Identities and Perceptions (Introduction by D'Lane R. Compton) --
1. Blogging My Academic Self: Jenny Davis --
2. The Gendered Characteristics of Facebook Interaction : Nathalie Delise --
3. Negotiating Gay Male Christian Identities: Brandi Woodell --
4. Tomboys in the Work of Carson McCullers: Emily Knox --
Part II: Culture, Stereotypes, and Stigma (Introduction by D. Nicole Farris) --
5. Violent Environment: Women and Frontier Coffey County, Kansas: 1855-1880 (Lisa Bunkowski, and Amanda Hedstrom --
6. Gender Specific Stereotypes in Television Advertisements: D. Nicole Farris --
7. Carmen Tafolla: Chicana Writer, from the Whispers of Her People: Manuel Medrano --
8. The Social Construction and Resistance of Menstruation as a Public Spectacle: Ashly Patterson --
9. Race, Gender, and Sexuality in Cyberspace: Jesus Smith --
Part III: Social Problems and Applications (Introduction by Mary Ann Davis) --
10. Punishing Abused Women: A Retrospective on a Ms. Magazine Blog: Dianne Bartlow --
11. Constructing Gay Male and Lesbian Foster Families: Mary Ann Davis --
12. Sex Differences in Adult Mortality: Some Evidence from Taiwan and the United States: Yu Ting Chang --
13. Gendered Helping Behaviors and Place Attachment in New Orleans' Upper 9th Ward: Jenny Savely.
Includes bibliographical references and index.
ENH
Trim Education
Keywords: Social perception; Stereotypes (Social psychology); Identity (Psychology); Sexism; English language